Clinically occult image revelations of fluorodeoxyglucose positron emission tomography/computed tomography in a peculiar case of sinonasal myeloid sarcoma - Mathew, Shema; Muthukrishnan, Indirani; Simon, Shelley (World Journal of Nuclear Medicine, 2021)
Myeloid sarcoma (MS) is a sparse association of acute myeloid leukemia (AML) with poor overall survival. Sinonasal involvement in MS is rarer and meagerly studied. Recent prospective studies have underlined the importance of positron emission tomography/computed tomography (PET/CT) in disease assessment and relapse detection in extramedullary (EM) AML. Herein, we report a case of MS with sinonasal, orbital, dural, breast, pleural extent of disease with sacral neural foraminal compression. Initial histopathologic and clinicoradiologic features had pointed toward lymphoma. Immunohistochemistry (IHC) on the contrary revealed MS. Although the role of IHC in asserting the diagnosis of MS is remarkable, PET/CT surpasses other modalities in early detection of EM sites of involvement, overall assessment of disease burden, targeting therapy, prognostication, and relapse recognition. Inclusion of PET/CT as a baseline imaging modality can be beneficial in tailoring patient management to improve survival and overall quality of life.
Keywords: Immunohistochemistry; positron emission tomography in extramedullary acute myeloid leukemia; positron emission tomography in myeloid sarcoma; sinonasal myeloid sarcoma